2020
DOI: 10.1080/00324728.2020.1750677
|View full text |Cite
|
Sign up to set email alerts
|

All-time low period fertility in Finland: Demographic drivers, tempo effects, and cohort implications

Abstract: The ongoing period fertility decline in the Nordic countries is particularly strong in Finland, where the total fertility rate (TFR) reached an all-time low of 1.41 in 2018. We analyse the decrease in Finland's TFR in 2010-17, and assess its consequences for cohort fertility using complementary approaches. Decomposition of this fertility decline shows that first births and women aged <30 are making the largest contributions. However, women aged 30-39 are also, for the first time in decades, experiencing a sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 47 publications
1
53
0
2
Order By: Relevance
“…Whereas some years ago the literature (prudently) forecast a slight rebound in completed fertility in Northern and Western Europe (Schmertmann et al 2014), more recent research suggests instead that, at least for Finland, the all-time low period fertility currently observed is not a consequence of accelerating fertility postponement. Rather it is most likely a sign of a decreasing fertility quantum (Hellstrand, Nisén, and Myrskylä 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some years ago the literature (prudently) forecast a slight rebound in completed fertility in Northern and Western Europe (Schmertmann et al 2014), more recent research suggests instead that, at least for Finland, the all-time low period fertility currently observed is not a consequence of accelerating fertility postponement. Rather it is most likely a sign of a decreasing fertility quantum (Hellstrand, Nisén, and Myrskylä 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This trend may be partly explained by the postponement 4 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 of the first birth until higher ages. However, throughout the decade, fertility fell in all age groups between and 40, which indicates a pattern of suppression rather than of postponement (Hellstrand, Nisén and Myrskylä 2020). Moreover, as such a prolonged decline in births among women aged 30 and above has not been previously observed in the Nordic countries, it appears to signal some changes that go deeper than postponement.…”
Section: Falling Fertility In the Nordic Countriesmentioning
confidence: 63%
“…Indeed, around three-quarters of the decline in fertility in the 2010s can be attributed to women having fewer first children (Hellstrand, Nisén and Myrskylä 2020;Roustaei et al 2019). This trend may be partly explained by the postponement 4 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 of the first birth until higher ages.…”
Section: Falling Fertility In the Nordic Countriesmentioning
confidence: 99%
“…Lastly, fertility by parity is important for understanding the relationship between uncertainty and space. Declines in first births before age thirty and declines in higher order births after age thirty are demonstrably related to recent fertility declines (Goldstein et al 2013;Hellstrand et al 2020a). Our analysis only accounts for total fertility by age.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Nordic countries were not among these countries and fertility decline in the Nordic regime of established family support policies and high levels of gender equality are in stark contrast to relatively high period fertility throughout the 1990s and 2000s (Andersson et al 2009;Hellstrand et al 2020a). Decreases in first birth rates and fertility at younger ages appear to be driving these unprecedented changes in the Nordic countries (Hellstrand et al 2020a) and research has proposed a number of factors to explain fertility change in the Nordic countries (Jalovaara et al 2019;Nisén et al 2020). Most importantly, many researchers have suggested that increasing economic and social uncertainty is negatively related to fertility (Goldstein et al 2013;Comolli et al 2019).…”
Section: Introductionmentioning
confidence: 99%